2020
DOI: 10.3389/fmicb.2020.00082
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Analysis of a Novel Strain of Taiwan Hot-Spring Cyanobacterium Thermosynechococcus sp. CL-1

Abstract: Thermosynechococcus is a genus of thermophilic unicellular cyanobacteria that are dominant in microbial mats at about 50-65 • C in alkaline hot springs of eastern Asia. We used PacBio SMRT Sequencing to sequence the complete genome of a novel strain of thermophilic cyanobacterium, Thermosynechococcus sp. CL-1, isolated from the Chin-Lun hot spring (pH 9.3, 62 • C) in Taiwan. Genome-scale phylogenetic analysis and average nucleotide identity (ANI) results suggested that CL-1 is a new species in the genus Thermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 49 publications
5
21
4
Order By: Relevance
“…Running proteinortho analyses with the seven genus level Thermosynechococcus and the six family level sequences, the overall core is reduced by just over 30%, from 1878 to 1283 CLOGs. This number of ~1900 core CLOGs within the genus is different from a recent analysis (Cheng et al, 2020), with the higher number observed here being due to the inclusion of the newly available and revised T. elongatus PKUAC-SCTE542 genome. Shared genes, not core genes, comprise a larger percentage of the genomes for smaller genomes, while unique genes are abundant in larger genomes (Figure 2a).…”
Section: Thermosynochococcaceaecontrasting
confidence: 99%
See 2 more Smart Citations
“…Running proteinortho analyses with the seven genus level Thermosynechococcus and the six family level sequences, the overall core is reduced by just over 30%, from 1878 to 1283 CLOGs. This number of ~1900 core CLOGs within the genus is different from a recent analysis (Cheng et al, 2020), with the higher number observed here being due to the inclusion of the newly available and revised T. elongatus PKUAC-SCTE542 genome. Shared genes, not core genes, comprise a larger percentage of the genomes for smaller genomes, while unique genes are abundant in larger genomes (Figure 2a).…”
Section: Thermosynochococcaceaecontrasting
confidence: 99%
“…Thermosynechococcus with genomes available are from hot springs which vary in temperature from 44 -94 °C, pH ranging from 5.4 -9.3, sulfate concentrations between 0.06 mM and 17.4 mM and iron concentrations between 0.0004 mM and 0.261 mM (Table 1) at their source. It is noteworthy that for two of the genomes -those from Okuoku-hachikurou and Jinata hot springs -the ferrous iron concentrations at the source by far exceed those at the other springs with 114 µM at OHK and 261 µM at Jinata Cheng et al, 2020).…”
Section: Tokyo Japan)mentioning
confidence: 96%
See 1 more Smart Citation
“…Interestingly, multivariate analyses, which were used to investigate the relationship between abundances, physico-chemical and geographic features, revealed that the cyanobacterial community composition was positively correlated with the hot spring location (Mantel statistic = 0.19, p-value = 9 × 10 −4 ), but not with physicochemical parameters, such as temperature or pH (Mantel test, p-value > 0.01). For example, MAGs from the PCC-7336 order were more abundant in North American samples, while Thermosynechococcales MAGs were found mainly in Asian samples independent of hot spring conditions (Supplementary Figure 3), thereby corroborating the proposed biogeographical islands for these unicellular cyanobacteria (Papke et al, 2003;Cheng et al, 2020). The correlation between community composition and geographical location was also observed through non-metric multidimensional scaling and cluster analyses ( Supplementary Figures 2B,C).…”
Section: Cyanobacterial Mag Abundances In Hot Spring Metagenomessupporting
confidence: 67%
“…The latter strain provides an example of the dangers of relying on strains that exhibit potentially non-representative phenotypes with the isolation of S. elongatus UTEX 3055, a very close relative of S. elongatus PCC 7942, indicating that freshwater Synechococcus may be motile and natively community-forming. Thermosynechococcus vulcanus NIES-2134 (RKN) and Thermosynechococcus elongatus BP-1 similarly are very closely related [ 135 ] and yet show divergent aggregation phenotype, with T. elongatus BP-1 being deficient in aggregation [ 136 ], illustrating the importance of selecting appropriate strains for research. The examples of S. elongatus PCC 7942 and N. punctiforme have demonstrated that much is left to be understood about the secretory roles of the T4P apparatus in cyanobacteria, providing potential avenues of cell–cell communication which have so far been largely missing in the phylum.…”
Section: Discussionmentioning
confidence: 99%